Race and ethnicity moderate the associations between lifetime psilocybin use and past year hypertension - Jones, Grant M.; Ricard, Jocelyn A.; Nock, Matthew K. (Frontiers in Psychiatry, 2024)
Background Hypertension is a major source of morbidity and mortality worldwide, particularly for racial and ethnic minorities who face higher rates of hypertension and worse health-related outcomes. Recent research has reported on protective associations between classic psychedelics and hypertension; however, there is a need to explore how race and ethnicity may moderate such associations. Methods We used data from the National Survey on Drug Use and Health (2005–2014) to assess whether race and ethnicity moderate the associations between classic psychedelic use – specifically psilocybin – and past year hypertension. Results Hispanic identity moderated the associations between psilocybin use and past year hypertension. Furthermore, individuals who used psilocybin and identified as Non-Hispanic White had reduced odds of hypertension (aOR: 0.83); however, these associations were not observed for any other racial or ethnic groups in our study for individuals who used psilocybin. Conclusion Overall, our results demonstrate that the associations between psychedelics and hypertension may vary by race and ethnicity. Longitudinal studies and clinical trials can further advance this research and determine whether such differences exist in causal contexts. Project registration https://osf.io/xsz2p/?view_only=0bf7b56749034c18abb2a3f8d3d4bc0b.